2008
DOI: 10.1016/j.expneurol.2008.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Maintaining epitheliopoietic potency when culturing olfactory progenitors

Abstract: The olfactory epithelium is remarkable for the persistence of multipotent, neurocompetent progenitor and stem cells throughout life that can replace all of the various cell types of the epithelium following injury. The therapeutic exploitation of the neurocompetent stem cells of the adult olfactory epithelium would be facilitated by the development of a culture system that maintains the in vivo potency of the progenitors while they are expanded and/or manipulated. We have used an air-liquid interface culture p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 46 publications
3
27
0
1
Order By: Relevance
“…As mentioned above, we found that suspension or sphere cultures grew poorly with attempted passaging, consistent with prior reports (Jang et al, 2008;Krolewski et al, 2011). Therefore, we transitioned to adherent substrates, such as vitronectin, but found cells remained difficult to expand with standard neurosphere medium (Reynolds and Weiss, 1992).…”
Section: Gbcs Expand In Culture When a Tgfβ Receptor Is Blockedsupporting
confidence: 86%
See 3 more Smart Citations
“…As mentioned above, we found that suspension or sphere cultures grew poorly with attempted passaging, consistent with prior reports (Jang et al, 2008;Krolewski et al, 2011). Therefore, we transitioned to adherent substrates, such as vitronectin, but found cells remained difficult to expand with standard neurosphere medium (Reynolds and Weiss, 1992).…”
Section: Gbcs Expand In Culture When a Tgfβ Receptor Is Blockedsupporting
confidence: 86%
“…Despite formation of primary spheres in standard neurosphere medium, attempts at expanding sphere-forming cultures were unsuccessful, consistent with prior reports (Jang et al, 2008). Thus, we abandoned floating cultures and allowed cultures derived Table 1 and Fig.…”
Section: Basal Cell Isolationsupporting
confidence: 72%
See 2 more Smart Citations
“…In such cultures, Sus cells can be visualized as coherent epithelial sheets in which virtually all cells express cytokeratin 18 (CYT18; also known as keratin 18); Fig. 7D shows CYT18 staining of Sus cells in the OE in vivo (see Pixley, 1992;Jang et al, 2008). To determine the effects of ACTB and GDF11 on Sus cell development in vitro, cultures were grown for 48 hours in the presence or absence of these factors.…”
Section: Research Articlementioning
confidence: 99%